Association Between Weight Control Behaviors and Diet Quality Among Brazilian Adolescents and Young Adults: Health Survey of São Paulo with Focus on Nutrition, 2015 - De Moraes-Ferrari, G (Springer Science and Business Media Deutschland GmbH, 2022)
Purpose: Little is known about how behaviors to control weight are associated with diet quality among youth from low- and middle-income countries. The aim of this study was to examine associations between efforts to control weight (ECW) and diet quality among Brazilian adolescents and young adults. Methods: Data from 731 participants (17.89 ± 4.92 years, 51.1% female) of the 2015 Health Survey of São Paulo were used for this cross-sectional study. Dietary intake was assessed using a 24 h dietary recall and diet quality was calculated using the Brazilian Healthy Eating Index—Revised (BHEI-R). Participants reported their ECW, weight satisfaction, and socio-demographics. Descriptive statistics and linear regressions were calculated to investigate associations between ECW and diet quality. Results: Approximately 47.7% of participants were dissatisfied with their current weight, and 41.0% reported ECW. Reported strategies to control weight included increased physical activity, taking care of what they eat, and dieting (8.2, 3.1, and 2.5%, respectively). After adjusting for age, sex, race/ethnicity, and body mass index, reporting at least one ECW (ß = 0.08; 95% CI 0.02, 0.13), taking care of what to eat (ß = 0.15; 0.08, 0.22) and being satisfied with their weight (0.08; 0.02, 0.13) were all associated with a higher overall BHEI-R score. Conclusion: Overall diet quality score showed a small increase in participants reporting ECW. Further studies should be conducted to provide strategies used by adolescents from low- and middle-income countries to control their weight. Thus, developing public health policies, and behavioral-change strategies. Level V: Cross-sectional descriptive study. © 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.